Direct anterior total hip arthroplasty with dual mobility cup for femoral neck fractures in dementia patients - Okuno Ryuji; Baba Tomonori; Ozaki Yu; Homma Yasuhiro; Kaneko Kazuo; Ishijima Muneaki (SICOT-J, 2025)
Background: Dementia patients with femoral neck fractures (FNFs) are unable to understand their dislocated limb positioning, which may impair rehabilitation and result in poorer functional recovery. Recently, good clinical results have been reported for the direct anterior approach for total hip arthroplasty (DAA-THA) using a dual mobility cup (DMC) for displaced FNFs. This study aimed to investigate differences in the clinical outcome of THA for displaced FNFs in patients with and without dementia. Methods: This study was retrospective and included 151 patients who underwent DAA-THA with DMC for displaced FNFs. Patients diagnosed with dementia prior to injury were classified into a dementia group (43 patients) and a non-dementia control group (control group, 108 patients). The evaluation items were age, sex, body mass index (BMI), preoperative Fracture Mobility Score (FMS), waiting period, preoperative anesthetic assessment, blood loss, operation time, complications, 1-year mortality, and 1-year FMS after surgery. The FMS was scored as: walking alone: 1, walking with a cane: 2, walking with a walker: 3, hand-guided walking: 4, and wheelchair: 5. Results: Significant differences were found in age, weight, BMI, and operation time. Postoperative dislocation was not observed in both groups. FMS was compared before and after injury in three categories: (1) unchanged from before injury, (2) one rank down, and (3) two or more ranks down. No significant differences were found in any of these categories (p = 0.09). Functional outcomes showed no significant difference in mobility recovery. The 1-year mortality rate was 9.35% (16 patients), with no significant difference between the two groups (p = 0.17). Discussion: DAA-THA using DMC for displaced FNFs may have similar functional outcomes and mortality rates in both patients with and without dementia.